GABAA receptor currents recorded from Müller glial cells of the baboon (Papio cynocephalus) retina - Reichelt, Winfried; Hernandez, Miguel; Damian, Raymond T.; Kisaalita, William S. (Neuroscience letters, 1996)
The effect of γ-aminobutyric acid (GABA) application on acutely isolated, non-cultivated Muller glial cells from the baboon retina was studied using the whole-cell voltage-clamp technique. Application of GABA (0.1 mM) generated inward currents at a holding potential of −80 mV as well as an increase in current noise. The GABA-activated current had a reversal potential of 18.6 mV and was therefore supposed to be a. Cl− current (ECl = 5 mV). The GABAA receptor agonist muscimol (0.1 mM) elicited an inward current and bicucullin (0.5 mM), a blacker of the GABAA receptor, diminished the GABA responses in our experiments completely. Baclofen (0.1 mM), a GABAB agonist, neither had an effect when applied under conditions where the dominant Müller cell K+ currents were unblocked, nor when the K+ currents were blocked by application of Ba2+ (1 rnM). Glycine (0.1 mM) was ineffective as well. From these results we conclude that the baboon retinal Muller cells possess GABAA receptors. However, these have recently been discovered on skate Müller cells whereas GABAA receptors could not be found on Muller cells of guinea pig, pig, mouse, rat and rabbit.